The Process of Student's Mathematic Abstract from Spatial Intelligence - Khasanah, Nor; Nurkaidah, Nurkaidah; Dewi, Rosmala; Prihandika, Yusuf Arkham (Universitas Sebelas Maret, 2019)
Every student must have mathematical abstraction skills. Research with a qualitative approach aims to identify the mathematical abstraction process of students when working on geometric material problems in terms of spatial intelligence. By using a descriptive design, apart from the researcher as the main instrument, the mathematical abstraction test, the spatial intelligence test, and the interview reference were used as auxiliary instruments. A total of 6 students from class VIII were selected through purposive sampling technique which was taken from each category of spatial ability which had been classified into high, medium and low criteria. Based on data analysis, students' mathematical abstraction can be grouped into 4 levels, namely: recognition, representation, structural abstraction, and structural awareness. The conclusions of this study are: 1) students with a high level of spatial intelligence can achieve all four levels of mathematical abstraction characteristics and activities, namely recognition, representation, structural abstraction, and structural awareness. 2) students with moderate spatial intelligence can only achieve two levels of mathematical characteristics and abstraction activities, namely recognition and representation. 3) students with low-level spatial intelligence are only able to achieve one level of mathematical abstraction characteristics and activity, namely recognition where students are able to remember previous activities and experiences related to the problems at hand. This shows that students with moderate and low-level spatial intelligence do not have adequate abstraction skills in the concept of geometry.